2019
DOI: 10.1002/ecs2.2788
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the distribution of niche space and risk for a freeze‐tolerant ectotherm, Lithobates sylvaticus

Abstract: Many animals depend on stable below‐the‐snow (subnivium) conditions to survive winter in seasonally cold regions. Freeze‐tolerant ectotherms may experience increased ice content and/or energy expenditure in suboptimal subnivium conditions, with implications for overwinter survival and body reserves available for spring reproduction. We used a novel mechanistic modeling approach to explore effects of winter climate on the microclimate conditions, energy expenditure, and ice dynamics of the freeze‐tolerant, subn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 44 publications
3
35
5
Order By: Relevance
“…Some increases (up to 4.3 cycles) occurred in the northeast (Pennsylvania to Maine) and northwest (Michigan to Minnesota) of the study region by the mid-21st century, but these shrank by the late 21st century ( Figure S4). Peak winter ice contents in this study were higher than those simulated in Fitzpatrick et al (2019), where Wood Frogs did not freeze in a portion of the Upper Midwest and Great Lakes Basin study area. Fitzpatrick et al (2019) suggested that peak ice contents may have been underestimated because they used averaged daily climate data for the 10-year study period to simulate a 365-day "average year".…”
Section: Re Sultscontrasting
confidence: 62%
See 4 more Smart Citations
“…Some increases (up to 4.3 cycles) occurred in the northeast (Pennsylvania to Maine) and northwest (Michigan to Minnesota) of the study region by the mid-21st century, but these shrank by the late 21st century ( Figure S4). Peak winter ice contents in this study were higher than those simulated in Fitzpatrick et al (2019), where Wood Frogs did not freeze in a portion of the Upper Midwest and Great Lakes Basin study area. Fitzpatrick et al (2019) suggested that peak ice contents may have been underestimated because they used averaged daily climate data for the 10-year study period to simulate a 365-day "average year".…”
Section: Re Sultscontrasting
confidence: 62%
“…Peak winter ice contents in this study were higher than those simulated in Fitzpatrick et al (2019), where Wood Frogs did not freeze in a portion of the Upper Midwest and Great Lakes Basin study area. Fitzpatrick et al (2019) suggested that peak ice contents may have been underestimated because they used averaged daily climate data for the 10-year study period to simulate a 365-day "average year". This may have lessened the influence of extreme cold events, which are unlikely to occur on the same Julian days year to year.…”
Section: Re Sultscontrasting
confidence: 62%
See 3 more Smart Citations